Sanitized for your protection ebook - Pastis, Stephan (Timmy Failure, 2015)
Some surprising news sends Timmy Failure on a hilarious caper as the New York Times best-selling series continues. Behold! You are all about to be witnesses to greatness. In this fourth volume of Timmy Failure's memoirs, Timmy is forced to hit the road in a cross-country trip that includes Timmy's mom, Total the polar bear, Doorman Dave, and smells-like-a-tangerine criminal mastermind Molly Moskins. It's a world gone mad, where good becomes bad, and Timmy Failure is a condemned man. Someone call the authorities. . . .